2018
DOI: 10.1158/0008-5472.can-18-0030
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Mediated Knockout of DGK Improves Antitumor Activities of Human T Cells

Abstract: The efficacy of T-cell therapy is inhibited by various tumor-associated immunosuppressive ligands and soluble factors. Such inhibitory signals turn specific T-cell signaling pathways on or off, impeding the anticancer functions of T cells. Many studies have focused on PD-1 or CTLA-4 blockade to invigorate T-cell functions through CD28/B7 signaling, but obtaining robust clinical outcomes remains challenging. In this study, we use CRISPR/Cas9 to potentiate T-cell function by increasing CD3 signaling via knockout… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(99 citation statements)
references
References 54 publications
4
90
0
Order By: Relevance
“…Indeed, these approaches were demonstrated to reliably knock down the expression of PD1 and other checkpoint inhibitors or key signaling molecules [280][281][282][283] and further optimization has been performed to delineate proper conditions for CRISPR editing in primary T cells [284] showing the successful silencing of several checkpoint targets. Unexpectedly, Fraietta et al recently showed that in the case of a CLL patient that achieved complete remission when treated with anti-CD19 CAR T-cells, the insertion of the CAR transgene caused a disruption in the methylcytosine dioxygenase TET2 gene [285].…”
Section: Gene Engineering and Editing Platformsmentioning
confidence: 99%
“…Indeed, these approaches were demonstrated to reliably knock down the expression of PD1 and other checkpoint inhibitors or key signaling molecules [280][281][282][283] and further optimization has been performed to delineate proper conditions for CRISPR editing in primary T cells [284] showing the successful silencing of several checkpoint targets. Unexpectedly, Fraietta et al recently showed that in the case of a CLL patient that achieved complete remission when treated with anti-CD19 CAR T-cells, the insertion of the CAR transgene caused a disruption in the methylcytosine dioxygenase TET2 gene [285].…”
Section: Gene Engineering and Editing Platformsmentioning
confidence: 99%
“…Furthermore, immune checkpoint blockade of inhibitory receptors (PD-1, Tim-3, CTLA-4, LAG-3, DGK, FAS, etc.) postpones CAR T-cells exhaustion and reinforces them for clinical trials [ 99 ]. Both HLA knockout and immunosuppressive pathways blockade can be achieved by means of CRISPR without any detrimental immunological side-effects as observed during employment of blocking antibodies (Fig.…”
Section: The Deluxe Zone Of Cancer Therapy Where Crispr Meets Immunomentioning
confidence: 99%
“…The knock-out of the intracellular signaling molecule diacylglycerol kinase (DGK) using a CRISPR/Cas9-based strategy in EGFRvIII CAR T cells led to a significantly less sensitivity to TGF-β mediated suppression and did not show significant loss of effector function following repeated stimulation. These in vitro findings translated to in vivo studies in a mouse glioma model as tumor-bearing mice receiving double knock-out EGFRvIII CAR T cells had significantly reduced tumor burden with increased frequencies of tumor-infiltrating lymphocytes [93]. The-knock in of genes to enhance CAR T cell function has not yet been tested in glioblastoma [91].…”
Section: Strategies To Enhance the Efficacy Of Adoptive Transfer Of Ementioning
confidence: 99%